Single cell analyses identify a highly regenerative and homogenous human CD34+ hematopoietic stem cell population - Fernando Anjos-Afonso (Nature Communications, 2022)
The trajectories of hematopoietic stem cells (HSCs) during lineage commitment are complex. Here, the authors use single cell RNA-sequencing and xenotransplantation to uncover CD34 + EPCR + (CD38/CD45RA)- HSCs, which high repopulating and self-renewal properties.